Screening for major diseases in community pharmacies: a systematic review. (20th May 2013) - Ayorinde, Abimbola Adebukola; Porteous, Terry; Sharma, Pawana
Abstract: Objectives: The aim of this systematic review was to assess the published evidence about the feasibility and acceptability of community pharmacy‐based screening for major diseases. Method: Studies published between January 1990 and August 2012 involving community pharmacy‐based screening interventions, published in the English language, were identified from electronic databases. Reference lists of included studies were also searched. Key findings: Fifty studies (one randomised controlled trial, two cluster randomised studies, five non‐randomised comparative studies and 42 uncontrolled studies) were included. The quality of most of these was assessed as poor. Screening was mostly opportunistic and screening tools included questionnaires or risk assessment forms, medical equipment to make physiological measurements, or a combination of both. Few studies assessed the accuracy of pharmacy‐based screening tools. More than half of the screening interventions included an element of patient education. The proportion of screened individuals, identified with disease risk factors or the disease itself, ranged from 4% to 89%. Only 10 studies reported any economic information. Where assessed, patient satisfaction with pharmacy‐based screening was high, but individuals who screened positive often did not follow pharmacist advice to seek further medical help. Conclusion: Available evidence suggests that screening for some diseases in community pharmacies is feasible. More studies are needed to compare effectiveness and cost‐effectiveness of pharmacy‐based screening with screening by other providers. Strategies to improve screening participants' adherence to pharmacist advice also need to be explored. This systematic review will help to inform future studies wishing to develop community pharmacy‐based screening interventions.